THE RELATIONSHIP OF KNOWLEDGE REGARDING THE PREVENTION OF DIARRHEA INCIDENCE IN MOTHERS WITH TODDLERS IN THE WORKING AREA OF LAMPULO COMMUNITY HEALTH CENTER, BANDA ACEH CITY - Desreza, Nanda; Tharida, Maimun; Asmaina (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2022)
In Indonesia, diarrheal disease still frequently affects toddlers. In 2017, Lampulo Health Center in Banda Aceh City recorded 216 cases of diarrhea among toddlers. The objective of this study was to investigate the relationship between mothers' knowledge and the prevention of diarrhea in toddlers within the Lampulo Public Health Center's service area in Banda Alam Subdistrict, Banda Aceh, in 2019. This was a cross-sectional study with a target population of 216 toddlers. We selected 68 respondents using a proportional sampling technique. The research took place in the Lampulo Health Center's service area, Kuta Alam Sub-District, Banda Aceh City, from May 2 to May 22, 2019. The findings revealed several concerning statistics: 54.4% of children under five did not receive exclusive breastfeeding, 54.4% of toddlers had a poor diet (MP-ASI), 63.2% used contaminated water, 58.8% had inadequate handwashing practices, 60.3% used unsanitary diapers (Jamaban), 63.2% disposed of baby stool improperly, 64.7% of toddlers had not received measles immunization, 54.4% of mothers had insufficient knowledge, and 60.3% of mothers were unaware of how to prevent diarrhea. Statistical analysis yielded a P-value of 0.001, indicating a significant relationship between mothers' knowledge and the prevention of diarrhea in infants at the Lampulo Health Center in Banda Alam Sub-District, Banda Aceh City in 2019. We recommend that the Health Center implement the LROA (Layanan Pencegahan Diare pada Balita) program to provide diarrhea prevention services for toddlers by healthcare professionals to mothers with limited knowledge on the subject.